2021
DOI: 10.1172/jci143990
|View full text |Cite
|
Sign up to set email alerts
|

The 5α-reductase inhibitor finasteride reduces opioid self-administration in animal models of opioid use disorder

Abstract: Opioid use disorder (OUD) has become a leading cause of death in the US, yet current therapeutic strategies remain highly inadequate. To identify potential treatments for OUD, we screened a targeted selection of over 100 drugs using a recently developed opioid self-administration assay in zebrafish. This paradigm showed that finasteride, a steroidogenesis inhibitor approved for the treatment of benign prostatic hyperplasia and androgenetic alopecia, reduced self-administration of multiple opioids without affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…Stereotaxic surgery and microinjections. Stereotaxic surgery was performed as previously described (Cadeddu et al, 2021). Briefly, mice were anesthetized with xylazine/ketamine (20/80 mg•kg -1 , IP) and then placed onto a stereotaxic frame (David Kopf Instruments, Tujunga, CA, USA).…”
Section: Stress Proceduresmentioning
confidence: 99%
“…Stereotaxic surgery and microinjections. Stereotaxic surgery was performed as previously described (Cadeddu et al, 2021). Briefly, mice were anesthetized with xylazine/ketamine (20/80 mg•kg -1 , IP) and then placed onto a stereotaxic frame (David Kopf Instruments, Tujunga, CA, USA).…”
Section: Stress Proceduresmentioning
confidence: 99%
“…Recently, the group of Peterson reported that NHE1 inhibitors could reduce opioid self-administration in a zebrafish model. 49 Although preliminary, it could be very interesting to test whether this result is mediated by NHE1, or a direct allosteric effect on opioid receptors, or both simultaneously. Many GPCRs interact with the Na(+)/H(+) exchange regulatory cofactor (NHERF-1/2), which was originally characterized as a cAMP-dependent regulator of Na(+)/H(+) exchange (NHE).…”
Section: Discussionmentioning
confidence: 99%
“…163,164 Interestingly, the findings of antidopaminergic properties of finasteride also led to the discovery of other potential therapeutic application of 5αR inhibitors in animal models of other motor disturbances, such as levodopa-induced dyskinesias, 165,166 as well as in opioid use disorder. 167 It is worth noting that the antidopaminergic effects of finasteride are not associated with extrapyramidal side effects, such as catalepsy, 161 likely a result of the interference with D 1 , rather than D 2 dopamine receptor signalling.…”
Section: Preclinical Findingsmentioning
confidence: 99%
“…107 This possibility is indirectly supported by preliminary data indicating that finasteride reduces impulsivity 173 and pathological gambling. 157 In addition, we recently documented that finasteride also potently reduces opioid self-administration, 167 another response highly influenced by impulsivity. Assuming that AP can reduce the prefrontal control of striatal outputs, this mechanism may also be responsible for a disinhibitory effect, which may account for the exacerbation of impulsive behaviours in response to acute stress.…”
Section: Con Clus I On S and Future Direc Tionsmentioning
confidence: 99%